2020
DOI: 10.3390/biom10111513
|View full text |Cite
|
Sign up to set email alerts
|

Co-Application of Eugenol and QX-314 Elicits the Prolonged Blockade of Voltage-Gated Sodium Channels in Nociceptive Trigeminal Ganglion Neurons

Abstract: Local anesthetics (LAs) can completely block nociception by inhibiting voltage-gated sodium channels (VGSCs), and thus, blocking action potentials (APs) within sensory neurons. As one of the several LAs, eugenol is used for dental pain treatment. It reportedly features multiple functions in regulating diverse ion channels. This study aimed to investigate the long-lasting analgesic effect of eugenol alone, as well as that of the combination of eugenol as a noxious-heat-sensitive transient receptor potential van… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Eugenol is a popular painkiller and anesthetic used in dental practice. It has been found to inhibit voltage-gated sodium channels (VGSC) in the primary supply neurons of the teeth in various studies, including one based on a rat model [ 29 , 30 ].…”
Section: Anti-inflammatory and Analgesic Activities Of Eugenolmentioning
confidence: 99%
See 1 more Smart Citation
“…Eugenol is a popular painkiller and anesthetic used in dental practice. It has been found to inhibit voltage-gated sodium channels (VGSC) in the primary supply neurons of the teeth in various studies, including one based on a rat model [ 29 , 30 ].…”
Section: Anti-inflammatory and Analgesic Activities Of Eugenolmentioning
confidence: 99%
“… The anticancer, anti-inflammatory, and antioxidant mechanism of action of eugenol (own elaboration based on [ 1 , 3 , 4 , 7 , 14 , 15 , 16 , 28 , 29 , 30 , 31 , 32 ]). …”
Section: Figurementioning
confidence: 99%
“…Eugenol is a common pain reliever and anesthetic utilized in dentistry. Varied studies have observed that it hinders voltage-regulated Na + channels (VRSCs) in the mainstream neurons of the teeth [ 73 , 74 ].…”
Section: Eugenol Anti-inflammatory Agentmentioning
confidence: 99%
“…distributed throughout the nerve tissue (it is a highly lipophilic substance) 11 and by its effects on ion channels in neuronal cells. 12 Moreover, Barbas et al 15 verified that eugenol did not manage to promote central nervous system depression in tambaquis (Colossoma macropomum), and that it could have a potentially toxic effect on fish brains, given that it caused an intense neuronal excitability, with seizure patterns on electroencephalogram. On the contrary, MS-222 blocks sodium channels mostly in the muscles and, to a lesser degree, the potassium channels in nerve membranes, 36 which would explain the lesser damage in nerve tissue found in the fish exposed to this anaesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…11 Its anaesthetic properties are derived from its effects on the ionic channels of the neural cells related to nociception, neuronal peak generation and synaptics. 12 Eugenol is highly lipophilic and is quickly absorbed through the gills and skin. 13 Although it is a widely used anaesthetic in research involving fish, it is known that eugenol increases cortisol as a response, 14 and it could be potentially toxic to the fish brain.…”
Section: Introductionmentioning
confidence: 99%